2005
DOI: 10.1523/jneurosci.4276-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Dependent Inhibition of Human CytochromecOxidase by a Dimeric Conformer of Amyloid-β1-42

Abstract: In studies of Alzheimer's disease pathogenesis there is an increasing focus on mechanisms of intracellular amyloid-␤ (A␤) generation and toxicity. Here we investigated the inhibitory potential of the 42 amino acid A␤ peptide (A␤ 1-42 ) on activity of electron transport chain enzyme complexes in human mitochondria. We found that synthetic A␤ 1-42 specifically inhibited the terminal complex cytochrome c oxidase (COX) in a dose-dependent manner that was dependent on the presence of Cu 2ϩ and specific "aging" of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
210
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(226 citation statements)
references
References 45 publications
14
210
0
2
Order By: Relevance
“…The present study revealed that intraneuronal accumulation of A␤ could be sustained during exposure to the peptide, especially in mitochondria, as previously reported (10,12,(37)(38)(39)(40). Considerable studies over the past decade have emerged indicating that some intracellular enzymes, insulin-degrading enzyme, endothelinconverting enzyme (ECE)-1b and ECE-2, as well as membrane enzymes, such as neprilysin, ECE-1a, ECE-1c, ECE-1d, matrix metalloproteinase (MMP)-2, MMP-3, and MMP-9, can cleave A␤ at either a single or multiple sites and cleavage products of A␤ resulting from such catabolism are less likely to aggregate and are less neurotoxic than A␤ itself (41).…”
Section: Discussionsupporting
confidence: 90%
“…The present study revealed that intraneuronal accumulation of A␤ could be sustained during exposure to the peptide, especially in mitochondria, as previously reported (10,12,(37)(38)(39)(40). Considerable studies over the past decade have emerged indicating that some intracellular enzymes, insulin-degrading enzyme, endothelinconverting enzyme (ECE)-1b and ECE-2, as well as membrane enzymes, such as neprilysin, ECE-1a, ECE-1c, ECE-1d, matrix metalloproteinase (MMP)-2, MMP-3, and MMP-9, can cleave A␤ at either a single or multiple sites and cleavage products of A␤ resulting from such catabolism are less likely to aggregate and are less neurotoxic than A␤ itself (41).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we suggest that A␤ is inserted into the inner membrane after import and that only a small portion of the A␤ is loosely attached. Interestingly, the integration of A␤ into the inner membrane, where the respiratory chain complexes reside, is in line with results showing that A␤ 1-42 may cause inhibition of complex IV (21). On the other hand, it was reported that A␤ colocalize with the mitochondrial matrix protein Hsp60 in mouse and human brain samples (13).…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that in AD at an early stage there is already a reduction in the number of mitochondria (14), the brain glucose metabolism is decreased (15), and the activities of both tricarboxylic acid cycle enzymes (16) and cytochrome c oxidase (COX) are reduced (17)(18)(19)(20). In vitro studies with isolated mitochondria suggest that A␤ inhibits COX activity in a copper-dependent manner (21). Furthermore, mitochondrial A␤-binding alcohol dehydrogenase (ABAD) has been found to be up-regulated in neurons from AD patients (22), and A␤ has been shown to interact with ABAD, resulting in free radical production and neuronal apoptosis.…”
mentioning
confidence: 99%
“…The accumulation of APP across mitochondrial import channels inhibited the entry of nuclear-encoded cytochrome c oxidase subunits IV and Vb proteins, and was associated with decreased cytochrome oxidase and increased free radical production [2]. Based on recent findings of APP/Aβ and mitochondria [1,2,3,55,56,63,64,79,80,81,82]. we propose that mutant APP/Aβ enter mitochondria and interact with mitochondrial proteins, disrupt the ETC, increase ROS production, and inhibit the generation of cellular ATP (Fig.…”
Section: App/aβ Association With Mitochondriamentioning
confidence: 91%